Multiplex PCR annealing temperature optimization for the detection of Listeria monocytogenes - Barboza-Fallas, Luis (2019)
Listeria monocytogenes is an opportunistic intracellular pathogen that has become one of the most important causes of foodborne infections worldwide. Due to the importance of L. monocytogenes in public health many protocols for the identification and typing of this organism have been described, but for the most part they are very complex and long lasting. For this reason, a multiplex PCR was developed for the rapid and sensitive detection of this bacterium in different types of samples. The objective of the present study was to optimize the multiplex PCR technique for the identification of L. monocytogenes. Different annealing temperatures were tested to determine which has the highest specificity, avoiding nonspecific amplifications. Amplifications were obtained at 57 ° C and lower temperatures. It is concluded that the best temperature for tm is 57 ° C.